Skamliga överenskommelser - om pactum turpe, dess rättsliga innebörd och hantering i domstol - Yngvesson,Jesper (2019)
As a general principle in Swedish contract law, illegal or "immoral" contracts cannot be enforced by the judiciary system. Such contracts are referred to as pactum turpe. The reach of the principle and which contracts are to be classified as pactum turpe is unclear, especially with regard to the "immoral". Neither the legislative body nor courts have given much clarification or guidance on the matter. The principle has met wide criticism, to the extent that its further existence has been questioned. How the courts are to deal with such contracts from a procedural standpoint is equally unclear. The traditional view is that it should be perceived as a certain kind of procedural hindrance and that claims accordingly shall be dismissed if it is clear that they are based on an illegal or "immoral" contract. In order to determine that, however, the courts need to familiarize themselves with the substantive legal matter of the contract in order to decide whether or not to try the claim on its substantive merits. Therefore, the procedural and substantive matters are closely connected in cases of pactum turpe, to say the least. This thesis argues that the principle is yet to be completely excluded from Swedish law but that there are other, more suitable ways to deal with "immoral" contracts in substantial law. Such solutions, however, require that the claims are tried in courts to begin with.
Keywords: avtalsrätt; civilrätt; civilprocessrätt; pactum turpe